2020
DOI: 10.1016/j.sjbs.2019.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco smoking causes secondary polycythemia and a mild leukocytosis among heavy smokers in Taif City in Saudi Arabia

Abstract: Tobacco smoking is a common risk factor of cardiovascular diseases, cancers and heart health problems. In Taif, the number of secondary polycythemia patients is increasing dramatically and most of those patients are heavy smokers. Therefore, this study is an attempt to understand the pathophysiological mechanism behind that problem. Whole blood and serum samples were collected from forty healthy people and forty tobacco smokers, voluntary for this study. Complete blood counts revealed a significant increase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 28 publications
3
19
0
Order By: Relevance
“…Exposure to more than 7000 chemicals, especially carbon monoxide, nicotine, and tar, is attributed to the development of various diseases in a smoker. Hypoxia is associated with impaired gas exchange and decreased oxygen delivery due to carbon monoxide inhalation and the peripheral vasoconstriction effect of nicotine [9][10][11][12]. As a response to the hypoxic status, there is an increase in the hematological parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to more than 7000 chemicals, especially carbon monoxide, nicotine, and tar, is attributed to the development of various diseases in a smoker. Hypoxia is associated with impaired gas exchange and decreased oxygen delivery due to carbon monoxide inhalation and the peripheral vasoconstriction effect of nicotine [9][10][11][12]. As a response to the hypoxic status, there is an increase in the hematological parameters.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that smoking has both acute and chronic effect on hematological parameters. A number of studies have reported that smokers of both genders have significantly higher number of leukocytes and elevation in neutrophils, lymphocytes, leukocytes, monocytes, eosinophils and basophils [36]. Malenica, et al [49] showed severe adverse effects of cigarette smoking on some hematological parameters.…”
Section: Smoking Age Gender and Exposure Timementioning
confidence: 99%
“…Hematologic changes are often used as biological markers for medical surveillance and early detection of health problems connected to occupational exposure to ANTNP and Irrad, which, as stated above, lead to DNA damage and oxidative stress. These underlying mechanisms can affect the number and interrelationships of blood elements and lead to immunosuppression and, consequently, cytopenia [35][36][37][38]. On the other side, there are also other factors contributing to occupationally induced carcinogenesis such as non-targeted effects, inflammation and complex interaction between ionizing radiation, antineoplastic drugs and the immune system [39].…”
Section: Complete Blood Countmentioning
confidence: 99%
“…In the future, it is expected that this invasive insect pest could be a main, critical pest in the Taif or nearby regions in KSA. Its biological parameters, when feeding is on broad bean pods and/or rose flower buds, and these two food sources are cultivated at Taif and easily obtainable [50].…”
Section: Some Pests and Insects Ratesmentioning
confidence: 99%